A comparative study on the effectivity of audio vs. videogames distraction techniques during pediatric local anesthetic administration - Estrella, Ma. Regina P.
Dental fear, anxiety and short attention span are some of the difficulties dentists and clinicians have to deal with when treating a child patient. Behavior management techniques help to alleviate these difficulties. The aim of this study is to compare the effectivity of audio vs. videogame distraction techniques during pediatric local anesthesia administration. The research was conducted during two dental extraction missions in Mandaluyong and Las Pinas City. Twenty subjects, aged 6-10 years old were divided into two groups. Sex was also noted. In one group, audio distraction was used during pediatric local anesthesia administration and videogame distraction was used in the other group. Data collected were based on the Modified Behavior Profile Rating Scale and the Venham Fear Picture Test. The results were analyzed using the t-test and ANOVA to determine the effectiveness of the distraction techniques. The Pearson Coefficient of Correlation was used to determine the relationship between age and sex and the response of the child to the method of distraction. Results show that videogame distraction is a more effective medium, producing a significant difference in the Scores btained for behavior modification._There was no significant difference between the two distraction techniques in terms of fear reduction._There is a positive relationship between age and the responsiveness of the child to distraction techniques. Males display more cooperative behavior and females experience less fear and anxiety when distraction is applied.